Pre-treatment predictors of dropout from prolonged exposure therapy in patients with chronic posttraumatic stress disorder and comorbid substance use disorders - Belleau, Emily L.; Chin, Eu Gene; Wanklyn, Sonya G.; Zambrano-Vazquez, Laura; Schumacher, Julie A.; Coffey, Scott F. (Behaviour research and therapy, 2017)
Posttraumatic stress disorder (PTSD) and substance use disorders (SUDs) are commonly co-occurring disorders associated with more adverse consequences than PTSD alone. Prolonged exposure therapy (PE) is one of the most efficacious treatments for PTSD. However, among individuals with PTSD-SUD, 35–62% of individuals drop out of trauma-focused exposure treatments. Thus, it is important to identify predictors of PTSD treatment dropout among substance abusers with PTSD in order to gain information about adapting treatment strategies to enhance retention and outcomes. The current study explored pre-treatment predictors of early termination from PE treatment in a sample of 85 individuals receiving concurrent treatment for PTSD and a SUD in a residential treatment facility as part of a randomized controlled trial. The results indicated that less education and more anxiety sensitivity uniquely predicted PE treatment dropout. Demographic variables, PTSD severity, SUD severity, mental health comorbidities, and emotion regulation difficulties did not predict treatment dropout. These results suggest that adding pre-treatment interventions that address anxiety sensitivity, and promote social adjustment and cognitive flexibility, could possibly improve PE retention rates in clients with high anxiety or low education. •Examined predictors of exposure treatment termination in those with PTSD and SUD.•Lower levels of education uniquely predicted earlier treatment termination.•Higher anxiety sensitivity uniquely predicted earlier treatment termination.